Implementasi Kebijakan Pelaksanaan Program Beasiswa Pemuda Tangguh Pada Bagian Pemerintahan Dan Kesejahteraan Rakyat Sekretariat Daerah Kota Surabaya - Novalia, Intan; Handoko, V. Rudy; Indartuti, Endang (Innovative: Journal Of Social Science Research, 2024)
This study aims to analyze the implementation of the “Pemuda Tangguh Scholarship Program” carried out by the Government and Public Welfare Division of the Regional Secretariat of Surabaya City. The research employs a descriptive qualitative approach, with data collected through interviews, observations, and documentation to gain an in-depth understanding of the program’s execution and to identify supporting and inhibiting factors in its implementation. The study focuses on evaluating the implementation process of the program and its impact on high school students who are scholarship recipients, particularly those from economically disadvantaged backgrounds. The findings indicate that the “Pemuda Tangguh Scholarship Program” has made a positive contribution to improve educational access for students from low-income families. However, several challenges persist, including delays in fund disbursement and a lack of initiative from students in submitting monthly activity reports. The study also reveals that the program's success heavily relies on the support of various stakeholders, including schools and government institutions. The results of this research are expected to provide recommendations for enhancing the effectiveness of the scholarship program in Surabaya and to serve as a reference for the development of educational policies aimed at improving human resource quality through inclusive and equitable access to education.